2021
DOI: 10.1007/s40291-021-00532-8
|View full text |Cite
|
Sign up to set email alerts
|

Detecting ALK Rearrangement with RT-PCR: A Reliable Approach Compared with Next-Generation Sequencing in Patients with NSCLC

Abstract: Background Precise detection of anaplastic lymphoma kinase (ALK) rearrangement guides the application of ALK-targeted tyrosine kinase inhibitors (ALK-TKIs) in patients with non-small-cell lung cancer (NSCLC). Next-generation sequencing (NGS) has been widely used in clinics, but DNA-based NGS used to detect fusion genes has delivered false-negative results. However, fusion genes can be successfully detected at the transcription level and with higher sensitivity using RNA-based reverse transcription polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Kuang et al conducted an analysis of RT-qPCR and NGS for EML4-ALK detection, reporting a concordance rate of 95.16%. In approximately 5% of discordant samples, RT-qPCR further identified additional ALK fusions among those with negative NGS results [ 42 ]. Lu et al reported the incidence of EML4-ALK detected by IHC (9.51%), RT-qPCR (11.62%), and NGS (5.84%) [ 43 ], suggesting that RT-qPCR has the potential advantage in clinical scenarios for ALK fusion detection.…”
Section: Discussionmentioning
confidence: 99%
“…Kuang et al conducted an analysis of RT-qPCR and NGS for EML4-ALK detection, reporting a concordance rate of 95.16%. In approximately 5% of discordant samples, RT-qPCR further identified additional ALK fusions among those with negative NGS results [ 42 ]. Lu et al reported the incidence of EML4-ALK detected by IHC (9.51%), RT-qPCR (11.62%), and NGS (5.84%) [ 43 ], suggesting that RT-qPCR has the potential advantage in clinical scenarios for ALK fusion detection.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are still some limitations to the RT-dd PCR method developed in this study. Compared with the advantages of NGS in detecting various types of mutations (including new or unknown drug-resistant mutations) [23,24], RT-dd PCR can only detect specific known mutation sites and cannot discover new or rare mutations [25,26]. In addition, RT-dd PCR also requires larger sample sizes and higher mutation frequency to achieve more reliable results [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, not only pre-analytical and analytical conditions, but also the biology of carcinomas could contribute to increasing the percentage of false-negative, since it is well known that carcinoma, differently from STT [30], often express chimeric transcripts at low levels [1]. Other evidence is present in the literature that supports this, e.g., the comparison of RT-PCR with an NGS pipeline for the detection of EML4-ALK fusions in non-small cell lung cancer FFPE samples [38].…”
Section: Discussionmentioning
confidence: 99%